(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to evaluate the QoL of stage IV lung cancer patients treated with immunotherapy alone or in combination with chemotherapy and to analyze factors influencing QoL after treatment. Materials and Methods: This prospective descriptive study enrolled 33 patients with stage IV lung cancer treated either immunotherapy alone or combined with chemotherapy at Internal Medicine Department 2, K Hospital, from October 2022 to October 2023. Assessment of life quality was conducted using two validated instruments: the EORTC QLQ-C30 and EORTC QLQ-LC13 questionnaires. Results: The EORTC QLQ-C30 questionnaire showed significant improvement in all functional areas (physical functioning, role functioning, social functioning, emotional functioning, and cognitive functioning) and in certain symptom aspects (fatigue, pain, and dyspnea) after four cycles of immunotherapy (p < 0.05). Financial difficulties increased significantly when comparing before and after treatment (p < 0.05). According to the EORTC QLQ-LC13 questionnaire, symptoms of cough, dyspnea, pain, and peripheral neuropathy improved after four treatment cycles (p < 0.05). The patient’s performance status (PS) at the beginning of treatment was found to be related to patients’ quality of life after treatment. There was no significant difference in QoL between the monotherapy and combination therapy regimens, except for symptoms related to chemotherapy toxicity. Conclusion: Immunotherapy regimens, either as alone or in combination with chemotherapy, provide significant symptom relief and QoL improvement for patients with stage IV lung cancer after four cycles of treatment.